2020
DOI: 10.3926/jiem.2795
|View full text |Cite
|
Sign up to set email alerts
|

Green supply management and green marketing strategy on green purchase intention: SMEs cases

Abstract: Purpose: This study aims to analyze green supply chain management (GSCM) and green marketing strategies (GMS) to green purchasing intentions (GPI). This study conducts on craft SMEs in the Special Region of Yogyakarta, Indonesia. Design/methodology/approach: This study uses primary data which is obtained through questionnaires. The unit of analysis in this study is organizations and individuals. The sampling technique is purposing sampling, with the criteria of SMEs that conduct environmentally friendly produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 35 publications
3
55
0
3
Order By: Relevance
“…Green supply chain management is a supply chain that aims to reduce waste, improve ecosystem quality, eco-efficiency, and material recycling process. In practice, green supply chain management which is in the form of measures in terms of technology, installation of new equipment, providing training for the supplier, and allocating employees is aimed at earning significant profits by paying attention to environmental efficiency (Drohomeretski, Da Costa & De Lima, 2014;Sugandini, Muafi, Susilowati, Siswanti & Syafri, 2020). To increase the production of a company and due to the government regulations regarding environmental impacts, it obliges company managers to implement the green supply chain management concept (Khaksar et al, 2016).…”
Section: Green Supply Chain Managementmentioning
confidence: 99%
“…Green supply chain management is a supply chain that aims to reduce waste, improve ecosystem quality, eco-efficiency, and material recycling process. In practice, green supply chain management which is in the form of measures in terms of technology, installation of new equipment, providing training for the supplier, and allocating employees is aimed at earning significant profits by paying attention to environmental efficiency (Drohomeretski, Da Costa & De Lima, 2014;Sugandini, Muafi, Susilowati, Siswanti & Syafri, 2020). To increase the production of a company and due to the government regulations regarding environmental impacts, it obliges company managers to implement the green supply chain management concept (Khaksar et al, 2016).…”
Section: Green Supply Chain Managementmentioning
confidence: 99%
“…With a huge apprehension of global warming and the increasing pressure of environmental pollution, many organizations have engaged the way to become more socially responsible by developing green products. Environmental management has become a primary concern for small and medium enterprises businesses [1] The phenomena of green consumer behaviors have changed as a new model for marketers and academicians [2,3]. The modern idea of green marketing has emerged as a competitive tendency to grab and win customers' attention in the marketplace.…”
Section: Introductionmentioning
confidence: 99%
“…The hospitality industry needs to develop environmental management strategies to cope with the environmental requirements and their impact on supply chain operations [6]. This is also because the interest of the consumers with regards to the protection of the environment has been revitalized [7][8][9][10][11][12][13][14][15][16]. Ghosh (2010) also suggested that increased public attention and awareness have caused manufacturers to be environmentally responsible [17].…”
Section: Introductionmentioning
confidence: 99%
“…Traceability and monitoring of these processes are becoming more critical to assure the finished product value by using blockchain technology that allows designers, sellers, and final customers to track the shipments [19]. The researchers acknowledge that green marketing research is a critical issue related to the environment and needs to be addressed as a priority [16,20].…”
Section: Introductionmentioning
confidence: 99%